High‐pressure behavior and phase transition of jadarite, a promising B and Li mineral commodity. Issue 11 (30th July 2022) - Comboni, Davide; Battiston, Tommaso; Rumsey, Michael S.; Pagliaro, Francesco; Lotti, Paolo; Hanfland, Michael; Gatta, G. Diego
Abstract: The high‐pressure behavior of a natural jadarite (ideally LiNaSiB3 O7 (OH), a  ∼ 6.76 Å, b  ∼ 13.80 Å, c  ∼ 7.69 Å, β  = 124.09°, space group P 21 / c ) has been studied by in situ single‐crystal and powder synchrotron X‐ray diffraction up to 20 GPa, with a diamond anvil cell and using He as a hydrostatic pressure‐transmitting fluid. Between 16.57(5) and 17.04(5) GPa, jadarite undergoes a first‐order iso‐symmetric phase transition, which is reconstructive in character, with a Δ V of approximately ‐3%. The structure of the high‐pressure polymorph was solved and refined (to R 1  ∼ 4%). The isothermal bulk modulus of the low‐ P polymorph of jadarite is KV 0 =  55.0(5) GPa ( βV 0 = 0.0182(2) GPa –1 ), and its P ‐derivative is 3.84(9). The compressional anisotropy, derived along the three main crystallographic directions, is modest, with βa 0 : βb 0 : βc 0  = 1.23:1:1.23. The P ‐induced deformation mechanisms at the atomic scale, which lead to phase transition, are described.